NON-TAYLOR SERIES BASED POSITIONING METHOD FOR LOCATION BASED SERVICES (Journal of Information and Communication Technology, 2008)
Location Based Services (LBS) has gained increasing popularity in major cities. Due to blocking from man-made structures, the existing Global Positioning System (GPS) could not satisfy LBS applications, especially in street canyon and indoor surroundings. This has lead to the development of Assisted GPS (A-GPS) which can provide better service availability and accuracy gain. In the conventional positioning method, Taylor series expansion is applied to solve non-linear distance equations. This method requires an initial estimation of A-GPS receiver’s position. This paper investigates the positioning method for LBS based on hybrid E-OTD/GNSS. The proposed positioning method is non-Taylor series based. Therefore, it involves less complicated mathematical expansion and substitution. A flexible LBS positioning tool is developed which can generate position information in convenient way. It supports both Taylor series and non-Taylor series based positioning methods. The obtained results showed that the proposed non-Taylor series based positioning method can achieve better positioning accuracy.